Vehicles Agency Rental Online System - Kashmim, Abdulrahman Khaled Salmen; Rani, Mohammad Firdaus Che Abdul; Jegatheswaran, Reshiwaran (Journal of Applied Technology and Innovation, 2023)
Vehicles Agency Rental Online System is a web application for lending or borrowing a vehicle for a period of time. This system offers 24-hour service and offers different types of cars with different costs. These systems can improve the efficiency and convenience of the car rental process for both the agency and the customer.